2021
DOI: 10.1111/nph.17432
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive seasonal drought causes substantial species‐specific shifts in fine‐root longevity and spatio‐temporal production patterns in mature temperate forest trees

Abstract: Temperate forest ecosystems are exposed to a higher frequency, duration and severity of drought. To promote forest longevity in a changing climate, we require a better understanding of the long-term impacts of repetitive drought events on fine-root dynamics in mature forests.Using minirhizotron methods, we investigated the effect of seasonal drought on fine-root dynamics in single-species and mixed-species arrangements of Fagus sylvatica (European beech) and Picea abies (Norway spruce) by means of a 4-yr-long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 88 publications
3
22
0
Order By: Relevance
“…The low variation in absorptive‐root density in P. abies compared with F. sylvatica (Table S2) further suggests limited morphological adaptation of P. abies roots to drought. Together with the observed prolonged life span of P. abies roots in the surface soil (Zwetsloot & Bauerle, 2021), overall root functionality might have been reduced (Vetterlein & Doussan, 2016; Nikolova et al ., 2020) and P. abies might have lost its capability to control C release to a greater extent than F. sylvatica . Although the relationships between root exudation, root morphology and root life span (both in general and under drought) require further study, our findings indicate that drought stress will have a greater impact on rhizosphere processes in P. abies than F. sylvatica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low variation in absorptive‐root density in P. abies compared with F. sylvatica (Table S2) further suggests limited morphological adaptation of P. abies roots to drought. Together with the observed prolonged life span of P. abies roots in the surface soil (Zwetsloot & Bauerle, 2021), overall root functionality might have been reduced (Vetterlein & Doussan, 2016; Nikolova et al ., 2020) and P. abies might have lost its capability to control C release to a greater extent than F. sylvatica . Although the relationships between root exudation, root morphology and root life span (both in general and under drought) require further study, our findings indicate that drought stress will have a greater impact on rhizosphere processes in P. abies than F. sylvatica .…”
Section: Discussionmentioning
confidence: 99%
“…Trees respond to reduced water supply by modifying their belowground C allocation (Ruehr et al ., 2009; Hagedorn et al ., 2016; Hommel et al ., 2016) and potentially increase root exudation rates (Karst et al ., 2017; Karlowsky et al ., 2018; Preece et al ., 2018; de Vries et al ., 2019; Jakoby et al ., 2020). However, most studies only use single root branches – defined as ephemeral terminal branch orders – to describe a plant's exudation behavior, which does not consider changes in root growth, distribution, and longevity that can also be significantly altered under drought (Nikolova et al ., 2020; Zwetsloot & Bauerle, 2021). Allometric scaling of root exudates from a single root branch to the entire root system, while accounting for changes in root production and longevity, can advance our understanding of species‐specific belowground C allocation patterns during periods of drought and improve terrestrial biosphere models (Fatichi et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Selection of genotypes with resistance to drought will be an important criterion for future breeding strategy [73]. It is also necessary to replace spruce monocultures with spruce-beech-fir mixed forests [75,76], with Norway spruce presenting much better resistance to drought in mixtures with beech than in monocultures [77].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise, specifically aerobic and combined with resistance training, have been recognized as a potential intervention to modulate inflammatory profile in humans [ 80 , 81 , 82 ], with a particular emphasis in older adults, in reversing or attenuate immunosenescence in aging [ 83 , 84 , 85 ], as well as reducing the development of chronic diseases [ 86 ].…”
Section: Impact Of Exercise On Inflammatory Profile and Association With Clock Genesmentioning
confidence: 99%
“…A study on females with metabolic syndrome found that a 12 week-long aerobic exercise intervention promotes a decrease in IL-6 [ 88 ]. The role of IL-6 in the framework of exercise as an anti-inflammatory therapy for cancer cachexia is also very significant (reviewed in [ 86 ]).…”
Section: Impact Of Exercise On Inflammatory Profile and Association With Clock Genesmentioning
confidence: 99%